Nursing team knowledge on care for patients with fungating wounds - Fernanda Mateus Queiroz Schmidt; Flávia Firmino; Nariman de Felício Bortucan Lenza; Vera Lúcia Conceição de Gouveia Santos
ABSTRACT Objective: to evaluate the nursing team knowledge of a cancer hospital on care for patients with Malignant Fungating Wounds (MFW) and to analyze associated sociodemographic and educational factors. Method: an observational and cross-sectional study, conducted between September and October 2015, after approval by the Research Ethics Committee. A questionnaire was applied containing sociodemographic, educational and related components to the accomplishment of dressings, dressings choice and orientation. Data were analyzed by using Chi-square, Fisher's exact test, Student's t-Test and Pearson's correlation. Results: 37 professionals participated in the study, most of whom were technicians (56.8%), women (91.9%) and with a mean age of 32 years. The professionals presented 56.5% of correct answers. There were no statistically significant associations between sociodemographic/educational variables and number of correct answers. Conclusion: there was a lack of important knowledge about care for patients with MFW, which should guide strategies for the oncology staff training.